CHALLENGES OF TRANSLATING IDIOMS AND FIXED EXPRESSIONS (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
Translating idioms and fixed expressions is widely recognized as one of the most demanding aspects of cross-linguistic and intercultural communication. Idioms are expressions whose meanings cannot be deduced from the literal definitions of the individual words they contain; they are deeply embedded in the culture, history, humor, and worldview of a speech community. Fixed expressions, while often more syntactically regular, also present significant challenges when they do not follow the same grammatical or semantic patterns in the target language. These linguistic units frequently carry metaphorical or symbolic meanings that are context-dependent and culturally bound, making their accurate translation a complex task that goes beyond word for word equivalence.This article provides an in-depth analysis of the multifaceted challenges that translators face when rendering idiomatic and formulaic language into another tongue. It highlights the cognitive demands of identifying idiomatic language in context, the need for cultural competence to understand and convey intended meanings, and the translator’s role as a cultural mediator. Particular attention is given to the risks of literal translation, such as semantic distortion, cultural miscommunication, or unintended humor, and the strategies required to achieve dynamic equivalence ensuring that both the meaning and function of the original expression are preserved.The study draws upon examples from English, Russian, Uzbek, and other languages to demonstrate typical pitfalls and successful translation approaches. It also explores how idioms reflect unique cultural narratives and why their misinterpretation may affect not only the clarity but also the emotional impact of a text. Furthermore, the abstract examines the limitations of machine translation tools in dealing with figurative language and underscores the importance of human judgment and creative adaptation in translation. Ultimately, this article emphasizes that idiom and fixed expression translation is not merely a linguistic exercise but an act of intercultural negotiation requiring linguistic precision, cultural awareness, and artistic sensitivity.